Mukhtar Masood's flashback in the Context of 'Louh Ayam Aur Harf Shoq' - Maroof, Bushra; Yousafzi, Muhammad Altaf (Makhz (Research Journal), 2025)
The techniques of flash back in Urdu Literature are the most successful description is its physical qulity as it takes the audience back to the past world.It is a technique that brings back the episodes or events that have already occurred. Mukhtar Masood success fully exploited the flash back technique in his travelogues When a character in a story thinks about the present and feels like they are in the past and tries to connect the two times, it is called a flashback." "Luh-e-Ayam" is Mukhtar Masood's third important creation that brought him to the top. Harf Shoq is the fourth and final book by Mukhtar Masood. In Mukhtar Masood's travelogue, the past and the present walk side by side. The traveler's eyes remain focused on the events happening around him and his mind keeps turning the pages of the past, watching the processions there. And when he has seen the processions of the past, the processions of his homeland appear clear and distinct to him.